If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5x + 4) + x + 2 = 0 Reorder the terms: 2(4 + 5x) + x + 2 = 0 (4 * 2 + 5x * 2) + x + 2 = 0 (8 + 10x) + x + 2 = 0 Reorder the terms: 8 + 2 + 10x + x = 0 Combine like terms: 8 + 2 = 10 10 + 10x + x = 0 Combine like terms: 10x + x = 11x 10 + 11x = 0 Solving 10 + 11x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 11x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 11x = 0 + -10 11x = 0 + -10 Combine like terms: 0 + -10 = -10 11x = -10 Divide each side by '11'. x = -0.9090909091 Simplifying x = -0.9090909091
| 9x-(x-5)=2x-(43+x) | | 10y-y+10y= | | 5(25+8.50x)=5(26.75+9.75x) | | 9x-(x-5)=2x-(40+x) | | 15.5-5(1/10) | | 9x-(x-5)=2x-(45+x) | | 2x-5=8x*7-x | | Y+56=148 | | 16x+2+7x= | | 9x-(x-5)=2x-(49+x) | | 76-53= | | 9x-(x-5)=2x-(39+x) | | 9x-(x-5)=2x-(29+x) | | 4x-2y=150 | | 71/2x41/3 | | 9x-(x-5)=2x-(23+x) | | 4x6/12 | | 3x+11=4x-4 | | 9x-(x-5)=2x-(6+x) | | 6y=712 | | -1-5+-3m= | | (2+3i)+(c+di)=2+i | | 14d^2=-27d | | (-12x+4x)+(6-12)= | | 5x-2x+x=9+3x+10 | | 9(8+8g)= | | 20-2(1/2) | | 3(9x+2)+8-16x= | | .5x+.1x=8 | | 6/12÷6/6 | | 5a^2-4ab+16b=0 | | 2.3=43.7 |